Doença holandesa no Brasil: ensaios sobre taxa de câmbio, perfil exportador, desindustrialização e crescimento econômico - Verissimo, Michele Polline (2010)
The main goal of this PhD dissertation is to empirically investigate the Dutch disease hypothesis for the Brazilian economy from 1995 to 2009. In order to pursue this, the work examines the following question: Is there any evidence capable of corroborating the relationship between commodity export specialization and the real exchange rate appreciation in Brazil during the recent period? The hypothesis of the work is based on the argument that the trend towards exchange rate appreciation and the increase in international commodity price, especially since 2003, are key factors to propitiate the manifestation of the Dutch disease symptoms in Brazil. The analysis of such problem is developed in three interdependent essays. The first essay investigates the relation between exchange rate, commodity exports and economic growth based on the curse of natural resources literature. The next essay analyzes the relation between exchange rate and commodity prices according to the commodities currencies literature for countries with abundant natural resources. The last essay evaluates the impact of the exchange rate and commodity prices on the production and employment of industrial sectors in order to address possible evidence of deindustrialization. The results from the empirical investigation indicate some evidence in favor of the Dutch disease in Brazil through the significant role of exports and commodity prices, particularly food and raw material, to explain the exchange rate appreciation and the lower economic growth in the recent period. Furthermore there is a significant role of the increase in certain commodity prices (food and raw materials) to the exchange rate appreciation. Last but not least, there is evidence of the requirement to pursue a more competitive exchange rate to stimulate production and employment of specific industry sub-sectors while high commodity prices have a negative effect on industrial variables. In a broad sense, the results from this dissertation revealed the relevance of price and specific (food, raw materials, minerals and energy) commodity export indicators to capture symptoms of the Dutch disease in Brazil. Other than this, evidences are more robust to investigate this problem in a long run perspective, emphasizing the difficulty of other studies trying to address the Dutch disease in Brazil focusing on short run analysis.